Synthesis and evaluation of stearic acid based heterocyclic Schiff bases as biolubricant additives in epoxy karanja fatty acid 2-ethyl hexyl esters base oil - Kontham V.; Ansari K.R.; Padmaja K.V.; Madhu D. (My University, 2025)
Four novel stearic acid derived Schiff bases containing heterocyclic aromatic groups (furan, thiophene, pyrrole and pyridine) were synthesized in a three step reaction procedure. All the products were characterized by FT-IR, NMR and ESI-MS. The lubricity and antioxidant properties of synthesized Schiff bases were evaluated with 4-ball machine and differential scanning calorimeter. The morphologies and composition of elements on the worn surfaces were studied by using scanning electron microscope and energy-dispersive X-ray spectroscopy. Results show that these stearic acid based derivatives possess good tribological properties and antioxidant performance. The difference in the additive performance of the derivatives is closely related to the difference in their molecular structure. Pyridine containing Schiff base was more effective as both antiwear and extreme pressure additive while thiophene derivative exhibited higher efficacy as antioxidant. © 2020 Elsevier B.V.